Excitatory synchronization of rat hippocampal interneurons during network activation in vitro - Pendeliuk, Viktoria S.; Melnick, Igor V. (Frontiers in Cellular Neuroscience, 2023)
Hippocampal interneurons (INs) are known to synchronize their electrical activity via mechanisms, which are poorly defined due to immense complexity of neural tissue but seem to depend on local cell interactions and intensity of network activity. Here, synchronization of INs was studied with intact glutamate transmission using paired patch-clamp recordings in a simplified culture model. The level of network activity was moderately elevated by field electric stimulation, which is probably an analogue of afferent processing in situ. In baseline conditions, spontaneous inhibitory postsynaptic currents (sIPSCs) were unitary events and ~45% of them coincided between cells within ±1 ms due to simple divergence of presynaptic axons. Brief network activation induced appearance of ‘hypersynchronous’ (~80%) population sIPSCs made up of several unitary events with jitter ±4 ms. Notably, population sIPSCs were preceded by transient inward currents (TICs). Those were excitatory events capable to synchronize firing of INs, in this respect being reminiscent of so-called fast prepotentials observed in early studies (Spencer and Kandel, 1961). TICs had network properties consisting of heterogeneous components: glutamate currents, local axonal and dendritic spikelets, and coupling electrotonic currents likely via gap junctions; putative excitatory action of synaptic GABA was not involved. Appearance of population excitatory-inhibitory sequences could be initiated and reproduced by firing of a single excitatory cell reciprocally connected with one IN. In summary, our data demonstrate that synchronization of INs is initiated and dominated by glutamatergic mechanisms, which recruit into supporting action other excitatory means existing in a given neural system.